1988
DOI: 10.1088/0029-5515/28/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Resonance absorption of ICRF waves in edge plasma

Abstract: A tokamak edge plasma significantly absorbs ICRF waves when a cutoff-resonance-cutoff is present in the evanescent region. Two ion component plasmas in a torus are considered although the plasmas are modelled by a slab. The absorption rate Ab is roughly given by M2 for 1 ≫ M2 > S2 and S4 for 1 ≫ S2 > M2, where M = kyℓ and S ≅ kzℓ and ℓ is a scale-length of the order of the plasma minor radius, and ky and kz are the perpendicular and the parallel components of the wave vector. It is noted that M and S become of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study of surface waves in a two-ion-species plasma is also relevant to the ion-cyclotron minority and mode-conversion heating schemes, as both schemes depend on the presence of two ion species in the plasma. The possible excitation of surface waves by antennas designed to excite the cut-off branches of the compressional Alfven wave has received considerable attention in recent years, since the excitation of such modes, and their possible absorption at the ion-ion hybrid-resonance surface (Messiaen et al 1984;Li et al 1985;Sugihara & Yamanaka 1988), could contribute to the higher-than-predicted proportion of the total power that is found not to be absorbed in the plasma centre (Steinmetz et al 1989), and the enhanced impurity production that is always observed during ion-cyclotron heating experiments (Bures et al 1988). Van Nieuwenhove et al (1987 have found experimental evidence for the parasitic excitation of surface waves during ion-cyclotron heating of a tokamak.…”
Section: Discussionmentioning
confidence: 99%
“…A study of surface waves in a two-ion-species plasma is also relevant to the ion-cyclotron minority and mode-conversion heating schemes, as both schemes depend on the presence of two ion species in the plasma. The possible excitation of surface waves by antennas designed to excite the cut-off branches of the compressional Alfven wave has received considerable attention in recent years, since the excitation of such modes, and their possible absorption at the ion-ion hybrid-resonance surface (Messiaen et al 1984;Li et al 1985;Sugihara & Yamanaka 1988), could contribute to the higher-than-predicted proportion of the total power that is found not to be absorbed in the plasma centre (Steinmetz et al 1989), and the enhanced impurity production that is always observed during ion-cyclotron heating experiments (Bures et al 1988). Van Nieuwenhove et al (1987 have found experimental evidence for the parasitic excitation of surface waves during ion-cyclotron heating of a tokamak.…”
Section: Discussionmentioning
confidence: 99%